2010
DOI: 10.1590/s1516-44462010000200016
|View full text |Cite
|
Sign up to set email alerts
|

Transtorno de identidade de gênero (TIG) e orientação sexual

Abstract: o próprio sexo e por um sentimento de inadequação no papel social deste sexo. Trata-se de uma condição que causa um sofrimento psicológico clinicamente significativo e prejuízos no funcionamento social, ocupacional ou em outras áreas importantes da vida de um indivíduo 1 . Desde a última metade do século XX, os avanços científicos têm favorecido o estudo deste transtorno, a maior aceitação social e a possibilidade de um tratamento integral orientado a redesignação sexual. Apesar disso, continua sendo pouco con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
1
Order By: Relevance
“…Furthermore, these individuals present a high rate of self‐mutilation, suicidal ideation, psychological pain, and economic hardship . Notwithstanding this, and despite many studies on psychiatric disorders in this population, the results are still controversial: some show a high frequency of psychiatric disorders and others affirm that these rates are comparable to those of the general population …”
mentioning
confidence: 97%
“…Furthermore, these individuals present a high rate of self‐mutilation, suicidal ideation, psychological pain, and economic hardship . Notwithstanding this, and despite many studies on psychiatric disorders in this population, the results are still controversial: some show a high frequency of psychiatric disorders and others affirm that these rates are comparable to those of the general population …”
mentioning
confidence: 97%
“…In this context, some scholars identifying TIG and depression in a woman with gender identity problems have found the association between these disorders and their history of prolonged exposure to incestuous abuse. [24][25] We realize that these implications are part of the daily lives of many women, resulting in intense suffering, which can lead to low self-esteem, depression, self-destructive behavior, sexual problems, homicidal ideas and suicide attempts. In relation to suicide, a research conducted with alcoholics who were abused in childhood found a significant association between suicide attempts and history of childhood sexual abuse, pointing to this experience as the strongest predictor of suicide attempts in alcohol-dependent individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A regulamentação destes procedimentos pressupõe suas finalidades terapêuticas, o que isentaria os profissionais da caracterização de suas intervenções como atos criminosos segundo o parâmetro do código penal (Val et al, 2009). Com a resolução a transformação cirúrgica da genitália interna e externa e caracteres sexuais não constitui crime de mutilação, pois passa a ter caráter terapêutico específico que busca adequar a genitália ao sexo psíquico.…”
Section: A Regulamentação Da Cirurgia De Transgenitalização No Brasilunclassified